The clinical and subclinical features of spinal cord injury on magnetic resonance imaging of patients with N2O intoxication - Tran Anh Tuan; Nguyen Minh Duc; Than Van Sy; Trinh Minh Hung; Tran Cuong; Nguyen Quang Anh; Vu Dang Luu; Pham Minh Thong (MDPI AG, 2020)
Nitrous oxide (N2O) is a weak anesthetic gas that was first used in 1844 in the field of dental anesthesia. However, currently, N2O is being abused for entertainment purposes in the form of N2O-filled balloons, called funky balls, which can cause many adverse effects, especially nervous system injury. This study aimed to investigate the detailed clinical and subclinical features associated with N2O intoxication. We retrospectively reviewed 47 patients diagnosed with N2O intoxication, from May 2018 to July 2019, and collected demographic data, clinical and laboratory tests, and spinal cord magnetic resonance imaging (MRI) findings. The mean time of funky ball use was 8.8 months, with a mean use of 36.3 balls per day. All patients presented with superficial sensory disorders. Reductions in muscle strength, decreased vibration sensation, and decreased or lost tendon reflexes were the most common clinical signs of N2O intoxication. Romberg sign and Lhermitte sign were observed in 39 patients (83%) and 21 patients (44.7%), respectively. Spinal cord lesions on MRI were observed in 32 patients (68.1%), which mostly presented with an inverted V sign. The total duration of N2O use, the number of days of using N2O per week, and the presence of Lhermitte sign (P<0.05) were significantly different between patients with and without spinal cord lesions on MRI. Serum levels of homocysteine and vitamin B12 were significantly different between the time of admission and discharge (P<0.05). Our study indicated that the days of using N2O per week was significantly associated with Spinal Cord Injuries (SCI) on MRI. According to the Receiver Operating Characteristic (ROC) curve analysis, a cutoff days of using per week value of 2.5 days could predict SCI with a sensitivity of 81.3%, a specificity of 73.3%, and an area under the ROC curve (AUC) of 0.813. Changes in the serum levels of homocysteine and vitamin B12 were effective markers for the evaluation of treatment response.